Performance enhancement scheme for IRS-assisted cognitive backscatter communication network - Bin LYU; Yi CAO; Jian LI; Ting QI (Tongxin xuebao)
In order to achieve the self-sustainable cognitive radio network （CRN） and improve its communication efficiency， an efficient multi-mode switching scheme assisted by the intelligent reflecting surface （IRS） for the overlay scenario was proposed.In particular， the secondary transmitter （ST） could work in either backscatter communication （BackCom） mode or harvest-then-transmit （HTT） mode.The IRS was exploited to enhance the energy harvesting， information backscattering， and information transmission efficiencies at the ST.To maximize the system sum-rate， an optimization problem about the phase shirts at the IRS， time scheduling， and power allocation was formulated.Since the formulated problem was non-convex， an efficient block coordinate descent （BCD） based algorithm was proposed to achieve the sub-optimal solution.Simulation results confirm that the proposed scheme can achieve up to 200% sum-rate gain over the benchmark schemes.